2016
DOI: 10.1038/srep33439
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Regions Associated With Interspecies Communication in Dogs Contain Genes Related to Human Social Disorders

Abstract: Unlike their wolf ancestors, dogs have unique social skills for communicating and cooperating with humans. Previously, significant heritabilities for human-directed social behaviors have been found in laboratory beagles. Here, a Genome-Wide Association Study identified two genomic regions associated with dog’s human-directed social behaviors. We recorded the propensity of laboratory beagles, bred, kept and handled under standardized conditions, to initiate physical interactions with a human during an unsolvabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 48 publications
0
48
0
Order By: Relevance
“…In this study, arvcf was identified in a sweep region on Ssa20 in both Dataset 1 and 2. The gene was previously associated with dog sociability to humans (Persson et al, 2016), while a paralog of dclk1 (doublecortin like) termed dcx (doublecortin) was found in a separate sweep on chromosome 20 that has been associated with tameness in foxes (Huang et al, 2015). A selective sweep on Ssa24 spans sema6a that is under selection in domestic cattle (Qanbari et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, arvcf was identified in a sweep region on Ssa20 in both Dataset 1 and 2. The gene was previously associated with dog sociability to humans (Persson et al, 2016), while a paralog of dclk1 (doublecortin like) termed dcx (doublecortin) was found in a separate sweep on chromosome 20 that has been associated with tameness in foxes (Huang et al, 2015). A selective sweep on Ssa24 spans sema6a that is under selection in domestic cattle (Qanbari et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that these specific traits are connected to deeper roots in animal sociality certainly merits further investigation. In addition, several genes in dogs that are associated specifically with dog-human social interactions have been implicated in humans as risk factors in neurological diseases affecting social interactions (autism and schizophrenia) (Persson et al, 2016). Ultimately, these sorts of investigations may lead to new insights on a matter that is receiving more and more attention, the question of whether humans can be regarded as a "self-domesticated" species (Brüne, 2007;Francis, 2015;Theofanopolou et al, 2017).…”
Section: Taking Stock and Looking Aheadmentioning
confidence: 99%
“…We remain convinced that when an obviously non-baited container is repeatedly cued by a human, dogs have great difficulty learning to completely distrust that person, still selecting the cued and empty container on about half of the trials. Dogs have been bred for thousands of years with attention directed to cues given by humans likely being a trait selected for in this breeding (Erdohegyi, Topal, Viranyi, & Miklosi, 2007;Miklosi et al, 2005;Perrson, Wright, Roth, Batakis, & Jensen, 2016). The survival value of such devotion to humans is, however, questionable.…”
Section: Discussionmentioning
confidence: 99%